Digital Literacy and Privacy Behavior Online. - Park, Yong Jin (Communication Research, 2013)
This study examined the impact of three dimensions of digital literacy on privacy-related online behaviors: (a) familiarity with technical aspects of the Internet, (b) awareness of common institutional practices, and (c) understanding of current privacy policy. Hierarchical regression models analyzed data from a national sample of 419 adult Internet users. The analyses showed strong predictive powers of user knowledge, as indicated by the three discrete dimensions, on privacy control behavior. However, the findings were mixed when accounting for the interaction between knowledge and Internet experiences. There were limitations on the extents of knowledge and action related to personalized information. Furthermore, those limitations divided with sociodemographic characteristics such as age, gender, income, and education. Ramifications for the current status of the FTC policy are discussed.